In Hamstring Muscles of Patients With Knee Osteoarthritis an Increased Ultrasound Shear Modulus Indicates a Permanently Elevated Muscle Tonus - Li, Feng; Wang, Zhen-Ya; Zhang, Zhi-Jie; Shen, Su-Hong; Guo, Jia-Yi; Guo, Yan-Xing; Feng, Yi-Ran; Zhang, Lin; Wen, Yong-Bing; Zhang, Yun-Fei; Fan, Yi-Ming; Fan, Meng-Meng (Frontiers in Physiology, 2022)
Some patients with knee osteoarthritis (KOA) show pain, shear modulus and limited flexion and extension at the back of the knee, leading to dysfunction and affecting life. This may be related to changes in the biomechanical properties of skeletal muscles. Shear wave elastography (SWE) can detect these changes by measuring muscle shear modulus. To investigate hamstring muscle shear modulus of healthy people and patients was studied using SWE method, and the correlation analysis between The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score of patients' subjective feeling and shear modulus of objective quantification was conducted. The hamstring shear modulus was measured by SWE in 50 patients and 50 healthy individuals. Pearson correlation coefficient was used to evaluate the correlation between hamstring shear modulus and shear modulus in patients. The hamstring shear modulus were significantly higher in the KOA group [the semimembranosus (SM) 15.23±7.23, the semitendinosus (ST) 15.94±5.40, the biceps femoris long tendinitis (BFL) 14.21±6.55) than in the control group（the SM 10.95±2.41,the ST 11.25±2.23, the BFL 9.98±2.81）(p=0.000, p=0.000, p=0.001). The hamstring shear modulus in the KOA group was moderately positively correlated with pain, shear modulus and physical function score. Preliminary results show that the shear modulus of the hamstring of KOA patients is higher than that of healthy people, the WOMAC score and the shear modulus of patients are moderately correlated. these preliminary results show that ultrasonic shear wave elastography measurement of shear modulus may be enough to sensitive, can detect these effects, more targeted in order to assist the doctor's diagnosis and treatment.